The nature, scope and purpose of spatial planning in South Africa : towards a more coherent legal framework under SPLUMA - Joscelyne, Kimberly (Institute of Marine and Environmental Law, 2016)
Planning law has a significant role to play in facilitating and governing development within a country. In South Africa, a shift has occurred from the utilisation of planning laws to regulating development, to facilitating it. A key area of this legal discipline is spatial planning, which determines the ideal utilisation and allocation of an area for certain land uses. The history of spatial planning in South Africa, and more specifically in the Western Cape, is an interesting one as the planning system that exists is fragmented and fraught with confusion. This has resulted in issues, confusion and conflicts which has resulted in numerous court cases. Previous attempts to reform the planning regime have proven to be somewhat unsuccessful as inherent challenges persist whilst new challenges have arisen. Prior to the introduction of the Constitution, spatial planning was utilised to promote Apartheid ideologies. In 1994 South Africa entered into a democratic era, entrenching equal rights and subjecting all laws to the Constitution. This had hefty impetus for spatial planning and its instruments which, to a large extent, were racially biased and therefore became unconstitutional. The legal regime governing spatial planning was tasked with addressing the ills of apartheid and simultaneously striving towards the goal of sustainable development. Issues and challenges have arisen, which have resulted in a fragmented and incoherent planning dispensation. These challenges and issues include the persistence of old order planning legislation and sector policies with activities operating parallel to the planning discipline. Consequently, there is overlap and confusion with regard to the purpose and legal status of spatial planning instruments. To address this at the national sphere, in 2013 contemporary planning reform was embarked upon, with the enactment of Spatial Planning and Land Use Management Act 16 of 2013 (SPLUMA). In light of recent planning reform triggered by the commencement of SPLUMA, the aim of this dissertation is to determine if SPLUMA provides a more coherent legal regime governing spatial planning in South Africa. This is pursued by understanding the role spatial planning has had in South Africa, by determining the nature, scope and purpose that spatial planning under the legal regime prior to SPLUMA. During Apartheid a dichotomy of planning systems existed, where different areas were governed by different laws which were underpinned by racial segregation. This resulted in significant issues of fragmentation and confusion. The transition to democracy brought about significant changes to the legal landscape, including planning as the nature, scope and purpose of spatial planning was tasked with addressing the ills of apartheid and promoting sustainability. Although legislative reform was triggered by democracy, clarity of the legal framework governing spatial planning did not occur. One of the contributing factors of this was the persistence of old order legislation and the spatial planning instruments it provided for. The commencement of SPLUMA has triggered wholesale reform which aims to provide a more coherent legal regime governing spatial planning. Positive strides towards this are evident, including the uniform approach which is applicable throughout South Africa that SPLUMA adopts.